The Role of Coffee Plantation in the Kerinci Regency Regional’s Economy - Suandi Suandi; Dompak Napitupulu; Endy Effran (SOCA: Jurnal Sosial Ekonomi Pertanian, 2020)
The main indicator in economy development was the role and contribution of each sector and or sub-sector to economic growth. One of the sub-sectors that had a major role and contribution in economy development was coffee plantations. To determine the role of coffee plantations on the community’s economy in Kerinci Regency, Jambi Province, therefore the research aims were (1) to determine the role of coffee plantations on income and employment, (2) to determine the contribution of coffee plantations to income and employment, and (3) to determine the ratio of coffee plantation growth to income and employment. The research was conducted in Kerinci Regency in 2015 with 6 months research period. The research data were sourced from secondary data, which was time series data from 2005-2013. Data were analyzed using the Location Qoutient (LQ) approach, and Shift-share. The results showed that coffee plantations in Kerinci Regency were the base sector. The analysis results obtained that coffee plantations played a role as the main driver of the Kerinci Regency’s economy because it had a high income and employment. During the period of nine years 2005-2013, economic growth, income and employment of coffee plantation in Kerinci Regency showed a positive ratio value though it was fluctuated.